Empowering Excellence Using Brain-Stimulating Articles and Interactive Sessions in a Coffee Knowledge WhatsApp Group - Maspul, Kurniawan Arif (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
This study delves into the efficacy of combining brain-stimulating articles with interactive sessions in a WhatsApp group to improve coffee knowledge and practice. The study, which draws on cognitive learning theory and practice-based learning theory, investigates how this strategy fosters a culture of continuous learning, collaboration, and mastery among baristas at Bash Coffee Company. Baristas actively develop knowledge and increase their understanding of coffee theory by offering properly picked articles. The articles include industry news, developing trends, and advanced methodologies, allowing baristas to properly encode, store, and retrieve coffee-related knowledge. The interactive sessions supplement article-based learning by promoting information exchange, concept clarification, and practical application. Baristas participate in real-world discussions, seek advice from expert facilitators, and share their experiences with others. This collaborative setting promotes development, innovation, and skill refining. The inclusion of brain-stimulating content and interactive sessions in the WhatsApp group enables baristas to excel in their coffee practice. This strategy not only improves knowledge, but also provides clients with unique coffee experiences. The study's findings provide useful insights for coffee firms looking to foster continuous learning and excellence in their baristas.